The Sandman. Vol. 11., Endless nights - Gaiman, Neil (The Sandman, 2019)
"In the final Sandman tale, Morpheus makes the ultimate decision between change and death. As one journey for the Endless ends, another begins for the Lord of Dreams and his family, bringing with it a time of reflection and a sad celebration. It's a wake in which friends and loved ones, relatives and rivals, fleeting lovers and immortal enemies gather to pay their respsects and to mourn their loss."--